The effect of cultivation conditions on the nitrogen fixation and seed yield of three Ukrainian varieties of soybean - Mykola Shevnikov; Olha Milenko; Ihor Lotysh; Dmytro Shevnikov; Oksana Shovkova (Наукові горизонти, 2022)
The relevance of the research topic is determined by the search for new technological methods of growing soybeans. Therefore, the specifics of the formation of productivity of different varieties of soybeans were investigated depending on a number of factors, such as: dates, methods of sowing and the rate of sowing. The purpose of the research was theoretical substantiation and practical advises of sowing dates and methods, sowing rates of different varieties of soybeans. Indicators of the influence of light intensity, fertilizer application, changes in seed sowing rates and different variants of soybean sowing distance on biological nitrogen fixation of soybeans were analyzed. As a result, regularities were established and a scientific substantiation of provisions was carried out, recommendations for production and scientifically based methods of soybean cultivation technology were developed, which ensure an increase in crop productivity by 15-25%. The developed practical recommendations for increasing soybean production are used in the farms of the region and beyond to solve an important problem − increasing the production of fodder and food protein and vegetable oil. Changing the sowing rate from 0.5 to 0.8 M seeds/ha for row sowing contributed to an increase in the attachment height of the lower beans, which, in turn, contributes to a reduction in crop losses during crop harvesting. Sowing rate had a greater influence on soybean yield than the sowing method. The best conditions were obtained when sowing 0.7 M seeds/ha of similar seeds. During the research, the Romantyka variety showed the highest yield of 3.07 t/ha under the row method of sowing, the sowing rate of 0.8 M seeds/ha and the second sowing period